Malignant Mediterranean spotted fever - Snehal Balvant Lunge; Vaibhav Patil; Sameer Ambar; Vishwas Naik (Wolters Kluwer Medknow Publications, 2015)
Fever with rash is one of the most common causes of referral to a dermatologist. A plethora of conditions need to be considered in the differential diagnosis. They may be broadly classified into infectious causes, drug reactions, and autoimmune disorders. Here we present a rare case of rickettsial fever with cardiac involvement in an elderly male patient with no comorbidities.